How to Increase Customer Satisfaction at Minimarket with using Servqual Analysis? - Hendy Tannady; Melly Moyana Jaya; James Candra; Ivan Dwi Darma; Steven Surya Wijaya (PT. EQUATOR SINAR AKADEMIA, 2023)
Service quality is one of the important things that must be considered in business because it plays an important role in increasing company productivity. This study was conducted to determine whether there is a gap between the performance of Indomaret Allogio Gading Serpong and the expectations of its customers. Research analyzes service quality using the gap analysis measurement method which is part of the Importance Performance Analysis (IPA) method. The method used is a quantitative method by conducting a survey using Google Form to 30 respondents who have made purchases at Indomaret Allogio Gading Serpong. The results of the study found that the availability of facilities, toilet cleanliness, and shopping convenience are the top priorities that must be improved. Then the completeness of the product, employee product knowledge, and employee service speed are important indicators to be maintained. Ease of parking and the beauty of the outlet interior are low priorities. The friendly attitude of employees and the ability of employees to answer questions are considered as excessive indicators.